Factors associated with the survival of adults with COVID-19 using a high-flow nasal cannula in a tertiary hospital in northern Peru during the second wave of the pandemic - Edwin Aguirre-Milachay; Darwin A. León-Figueroa; Cristian Díaz-Vélez; Mario J. Valladares-Garrido (PLoS ONE, 2025)
Objectives To identify factors associated with survival in patients admitted to the intensive care unit (ICU) for COVID-19 who used high-flow nasal cannula (HFNC) in a tertiary hospital in northern Peru during March to May 2021. Methodology A retrospective observational cohort study was carried out, including medical records selected according to established inclusion criteria. The dependent variable was survival, measured in days from admission to hospital discharge or death. Factors associated with survival related to demographic, clinical, laboratory, and imaging characteristics were investigated, as well as treatment-related parameters and variables associated with the use of HFNC. Hazard ratios (HR) were estimated to identify independent risk factors associated with survival. Results Of 154 patients, the mean age was 58.29 years. The most frequent comorbidities were arterial hypertension (29.2%), diabetes mellitus (20.6%), and obesity (17.4%). The median time of HFNC use was 5 days (interquartile range: 3–9 days). It was found that 32.2% of the patients required mechanical ventilation, and 51.6% died. The mean time of mechanical ventilation use was 15.1 ± 13.3 days. Survival was 97.5% at 48 hours, 85% at 7 days, 62% at 14 days, and 16.3% at the end of the study. Variables decreasing survival in patients with COVID-19 who were users of NFVC were age ≥ 60 years (HR = 2.23; 95% CI: 1.21–4.08), presence of arterial hypertension (HR = 1.87; 95% CI: 1.01–3.45), increased work of breathing on hospital admission (HR = 2.38; 95% CI: 1.31–4.35), and a ROX index (iROX) < 3.85 (HR = 1.71; 95% CI: 1.01–2.93). Conclusions Factors associated with survival were arterial hypertension and iROX < 3.85 with a mortality hazard of 1.5 times, age older than 60 years, and respiratory effort scale at admission WOB ≥ 4 points with more than twice the mortality hazard. The results of this study highlight the importance of early and accurate assessment of risk factors in patients with COVID-19 who use HFNC. Identifying these factors can help clinicians make more informed decisions and prioritize interventions that could potentially improve survival in this group of patients.